2020
DOI: 10.1186/s12885-020-6534-z
|View full text |Cite
|
Sign up to set email alerts
|

MammaPrint guides treatment decisions in breast Cancer: results of the IMPACt trial

Abstract: Background: Increased usage of genomic risk assessment assays suggests increased reliance on data provided by these assays to guide therapy decisions. The current study aimed to assess the change in treatment decision and physician confidence based on the 70-gene risk of recurrence signature (70-GS, MammaPrint) and the 80-gene molecular subtype signature (80-GS, BluePrint) in early stage breast cancer patients. Methods: IMPACt, a prospective, case-only study, enrolled 452 patients between November 2015 and Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…This is consistent with recent publication of the IMPACT trial by Soliman et al where the majority (77.5%) of the patients were cLow. 34 Some reasons for this might be the fee-for-service structure or the concern over litigation due to perceived undertreatment but these remain speculative. Currently guideline 1.7, published by ASCO on the use of biomarkers, advises against the use of MP in cLow patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with recent publication of the IMPACT trial by Soliman et al where the majority (77.5%) of the patients were cLow. 34 Some reasons for this might be the fee-for-service structure or the concern over litigation due to perceived undertreatment but these remain speculative. Currently guideline 1.7, published by ASCO on the use of biomarkers, advises against the use of MP in cLow patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multigene tests provide detailed insight into cancer biology with simultaneous information on expression of relevant, prognostic fundamental genes. Some assays are already used in diagnosis, as prognostic panels and for the prediction of treatment effects (mostly adjuvant or neoadjuvant systemic therapy) [ 173 ].…”
Section: Applications Of Transcriptome Analysis In Oncologymentioning
confidence: 99%
“…Similar results were reported in node-negative [ 113 ] but also node-positive early breast cancer [ 114 , 115 , 116 ]. The Prosigna © PAM50 [ 117 , 118 , 119 , 120 ] and EndoPredict © [ 121 ] assays also demonstrated a 20–35% decreasing of chemotherapy indications in HR+/HER2− early breast cancer.…”
Section: How Do Gene Expression Signatures Influence Clinical Decisions?mentioning
confidence: 99%
“…Several of the above-mentioned decision-making studies evaluated as secondary objectives the psychological impact of gene expression signatures. They demonstrated an improvement of physicians’ confidence regarding treatment recommendations [ 111 , 113 , 119 , 120 ], as well as a decreasing in patients anxiety and decisional conflict [ 112 , 116 , 117 , 118 , 120 , 121 ]. However, at least two studies showed that an unfavorable genomic result might increase anxiety, especially in a two-step decision making process [ 118 , 121 ].…”
Section: How Do Gene Expression Signatures Influence Clinical Decisions?mentioning
confidence: 99%